Pollen morphology of Scorzonera (Asteraceae) in Turkey - Pinar, Nur Münevver; Coşkunçelebi̇ Kami̇l; Şi̇mşek Derya; Okur, Seda; Makbul, Serdar; Acar, Aydan (Phytotaxa, 2016)
The pollen morphology of 45 taxa belonging to 15 sections of the genus Scorzonera distributed in Turkey were studied with light and electron microscopies. The pollen is generally 3-zonocolporate. Pollen grains are oblate-spheroidal with the polar axes 23.2–59.2 µm and the equatorial axes 27–62.5 µm. The outline is more or less circular to slightly elliptic in equatorial view and triangular or obtuse-hexagonal in polar view; amb semiangular to intersemiangular. Sculpturing is echinolophate. The spines are commonly concave-conical with a broad basis, sides are straight or slightly convex with a subacute tapered apical portion. Numerical analysis showed that polar axes, equatorial axes and exine thickness are valuable variables for seperating the examined taxa.